COMMODIFICATION OF POLITICAL AND RELIGIOUS VALUES IN THE MEDIA CONTEST IN INDONESIA - Mhd. Andi Syahputra; Aisyah Aisyah; Mailin Mailin (Universitas Dharmawangsa, 2021)
AbstractThis article discusses how religion has been commodified by a handful of people for their personal and group interests. In Indonesia itself, codification is carried out in the realm of politics and information media. Every general election, political actors compete to present themselves as best as possible in front of the public. The same thing also happened in the media in Indonesia, especially television. Television stations compete with each other in creating and presenting programs related to religious themes. Today, television is not only used as a tool in politics, but also in religion and economy. As one of the countries with the largest Muslim majority population, Indonesia is a profitable field for television stations. Islam is often used as a commercial commodity for reasons of great preference. This is what the author tries to raise in this study. How religion has been used as a profitable commodity to be traded, and used for the benefit of several parties. Keywords: Commodification; Media; Religion; Commercialism.